Notes from the Heroic Age of Antarctic Exploration: Gerald S. Doorly's songs of the 'morning - Philpott, C (Melbourne Conservatorium of Music, 2012)
This article explores the earliest known pieces of music composed directly in responseto Antarctica: a series of songs written by Gerald S. Doorly and John D. Morrison aboard the relief vessel Morning, which was sent from England to Antarctica to locate and re-supplyCaptain Robert Falcon Scott and company aboard the icebound Discovery in July 1902 as partof the British National Antarctic Expedition 1901-1904. These songs not only document thejourney south and the explorers Antarctic experiences; importantly, they also offer valuableinsight into a little-considered aspect of the history of Antarctic exploration - that is, what theexplorers did to entertain themselves and keep spirits high during long voyages at sea andfreezing cold, lonely nights in Antarctica.